Viola caipira no Brasil: uma história da técnica artesanal e cultura popular - Schafhauser, Lucas Guilherme (2018)
The present study focuses on the path taken by the viola caipira in Brazil, since its arrival with the Portuguese settlers until current days. We focus on verifying the affirmation of the musician Fernando Deghi: “This is the viola century”. For this, there were gathered information that points to the fact of the viola being or not on the rise. Our perspective is based on the point of view of the musical instruments making and perspective of the Dialogic Discourse Analysis (Mikhail Bakhtin and the Circle). We proceeded to the number of festivals that involved the viola caipira (search for posters in virtual media), the academic researches on and of viola caipira orchestras, observing if there was an increase in the search for the instrument in recent years. The universe of the viola caipira has been, until the end of the 20th century, object of little study. The instrument arrives in Brazil in the 16th century, but it remains in a non-erudite scenario, getting a place in music conservatory only in 1985. This distance is mainly related to the fact that the viola caipira has been predominantly an instrument of popular usage, particularly of the economically disadvantaged class’ culture and distant from the lifestyle of the large city, being often object of depreciation, satire and disqualification. In 1930, with the first recordings of viola songs and the interest from radio stations in country music, there was a first modern period of appreciation to the instrument. In the 1980s, emerges a great interest in the composition and musical performances for the viola, opening the range of use of the viola and attracting new characters this history. With the present work, we argue that the viola is, indeed, on the rise. We believe it is hasty to say that this will be the “century of the viola”, but we can assert that if its presence in society continues in this progression, the viola will be sitting on the same table as the most important musical instruments of this century. The trajectory of the viola occurs in a mostly monological musical environment, suppressing the voice of the viola, but this voice has strengthened and may come to position itself among the other musical instruments.